Yeast Hog1 proteins are sequestered in stress granules during high-temperature stress - Shiraishi, Kosuke; Hioki, Takahiro; Habata, Akari; Yurimoto, Hiroya; Sakai, Yasuyoshi (Journal of cell science, 2018)
The yeast high-osmolarity glycerol (HOG) pathway plays a central role in stress responses. It is activated by various stresses, including hyperosmotic stress, oxidative stress, high-temperature stress and exposure to arsenite. Hog1, the crucial MAP kinase of the pathway, localizes to the nucleus in response to high osmotic concentrations, i.e. high osmolarity; but, otherwise, little is known about its intracellular dynamics and regulation. By using the methylotrophic yeast Candida boidinii, we found that CbHog1-Venus formed intracellular dot structures after high-temperature stress in a reversible manner. Microscopic observation revealed that CbHog1-mCherry colocalized with CbPab1-Venus, a marker protein of stress granules. Hog1 homologs in Pichia pastoris and Schizosaccharomyces pombe also exhibited similar dot formation under high-temperature stress, whereas Saccharomyces cerevisiae Hog1 (ScHog1)-GFP did not. Analysis of CbHog1-Venus in C. boidinii revealed that a β-sheet structure in the N-terminal region was necessary and sufficient for its localization to stress granules. Physiological studies revealed that sequestration of activated Hog1 proteins in stress granules was responsible for downregulation of Hog1 activity under high-temperature stress. This article has an associated First Person interview with the first author of the paper.